2019
DOI: 10.1557/jmr.2019.145
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy states and mechanical properties of thermally cycled binary glasses

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
(75 reference statements)
0
23
1
Order By: Relevance
“…With increasing loading period, the energy difference increases, and the lowest value U 1 ≈ −8.358 ε is attained at T M LJ = 0.35 ε/k B when T = 500 000 τ . Interestingly, it was recently found that approximately the same value of the potential energy U ≈ −8.356 ε was obtained after 100 thermal cycles with the period T = 5000 τ and maximum temperature T M LJ = 0.35 ε/k B for the glass prepared with the cooling rate 10 −5 ε/k B τ [27]. These results suggest that the aging process, which is accelerated in the vicinity of T g , leads to the same energy decrease regardless whether the waiting time interval is continuous or discrete.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…With increasing loading period, the energy difference increases, and the lowest value U 1 ≈ −8.358 ε is attained at T M LJ = 0.35 ε/k B when T = 500 000 τ . Interestingly, it was recently found that approximately the same value of the potential energy U ≈ −8.356 ε was obtained after 100 thermal cycles with the period T = 5000 τ and maximum temperature T M LJ = 0.35 ε/k B for the glass prepared with the cooling rate 10 −5 ε/k B τ [27]. These results suggest that the aging process, which is accelerated in the vicinity of T g , leads to the same energy decrease regardless whether the waiting time interval is continuous or discrete.…”
Section: Resultsmentioning
confidence: 72%
“…In turn, recent atomistic simulations have shown that periodically loaded disordered materials evolve towards lower energy states at sufficiently small strain amplitudes, whereas the yielding transition and shear localization occur at large amplitudes after a number of transient cycles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In addition, it was found that amorphous materials subjected to multiple thermal cycles might either relax or rejuvenate depending on the thermal amplitude, number of cycles, and processing history [26][27][28]. However, the combined effect of thermal treatment and mechanical agitation on the potential energy, structure, and mechanical properties of amorphous alloys remains difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the results of numerical simulations have shown that the largest decrease of the potential energy and the increase in the yield stress occur for rapidly cooled glasses with the thermal amplitude not far below the glass transition temperature [29]. It was later found that after hundreds of thermal cycles with respect to a very low reference temperature, the glasses evolve into steady states, where particle dynamics becomes nearly reversible after each cycle, similar to the so-called limit cycles observed during athermal periodic shear of amorphous materials [17,19,30]. However, the dependence of the potential energy and mechanical properties on the preparation history, period and number of thermal oscillations, thermal amplitude, and reference temperature remains unexplored.…”
Section: Introductionmentioning
confidence: 73%
“…Notably, it was shown that thermal aging process in rapidly quenched glasses is facilitated by repetitive subyield cycling that leads to progressively lower levels of potential energy, and the effect is more pronounced at larger strain amplitudes [25,26,28]. More recently, it was found that relaxed states can be attained by repeatedly heating and cooling binary glasses at constant pressure with various thermal amplitudes below the glass transition [29,30]. In particular, the results of numerical simulations have shown that the largest decrease of the potential energy and the increase in the yield stress occur for rapidly cooled glasses with the thermal amplitude not far below the glass transition temperature [29].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously found that the nonaffine measure is particularly well suited for identification of localized shear transformations in quiescent and deformed disordered solids [40][41][42]. More recently, the analysis of nonaffine displacements was used to elucidate the structural relaxation dynamics and yielding during time periodic deformation [14, 16, 18, 20-22, 27, 30, 31] and thermal processing [43][44][45][46][47] 8]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%